A prospective observational study on feasibility of laparoscopic perforation repair in patients presenting with intestinal perforation at a tertiary care superspeciality hospital in Chhattisgarh - Taneja, Deepak; Gupta, Akash; Dave, Sandeep; Tamaskar, Siddharth (International Surgery Journal, 2020)
Background: Bowel perforation is one of the common emergencies faced by the surgeons in the developing world. It carries a high morbidity and mortality rate even today. In the present era, laparoscopy is being used as a better treatment alternative across the world. Various reports in literature are now available regarding the feasibility of laparoscopic repair of bowel perforation. The purpose of this study was to assess the feasibility of laparoscopic primary suture repair as the initial modality in treating a bowel perforation and to analyze the pattern of bowel perforation in relation to age, sex and etiology in Chhattisgarh state. Methods: This study included the data of relevant patients who got admitted in Ramkrishna Care Hospital Raipur from 1st October 2017 to 31st September 2019 (24 months). Results: Most commonly affected mean age group in this study was 39±15.82 years with male predominance. Statistically significant findings in favour of laparoscopic repair in our study were early return of bowel activity, less incidence of surgical site infection, early return to work (less hospital stay), less post-operative pain as compared to open surgery (p<0.05). Conclusions: In this study it was found that laparoscopy in patients with bowel perforation who are hemodynamically stable and present early (<72 hours) to the hospital is feasible and safe and gives many benefits including reduction in perioperative morbidity and mortality.